Peripheral cytokine and chemokine alterations in depression: a meta‐analysis of 82 studies. (25th January 2017) - Köhler, C. A.; Freitas, T. H.; Maes, M.; de Andrade, N. Q.; Liu, C. S.; Fernandes, B. S.; Stubbs, B.; Solmi, M.; Veronese, N.; Herrmann, N.; Raison, C. L.; Miller, B. J.; et al.
Abstract : Objective: To conduct a systematic review and meta‐analysis of studies that measured cytokine and chemokine levels in individuals with major depressive disorder (MDD) compared to healthy controls (HCs). Method: The PubMed/MEDLINE, EMBASE, and PsycINFO databases were searched up until May 30, 2016. Effect sizes were estimated with random‐effects models. Result: Eighty‐two studies comprising 3212 participants with MDD and 2798 HCs met inclusion criteria. Peripheral levels of interleukin‐6 (IL‐6), tumor necrosis factor (TNF)‐alpha, IL‐10, the soluble IL‐2 receptor, C‐C chemokine ligand 2, IL‐13, IL‐18, IL‐12, the IL‐1 receptor antagonist, and the soluble TNF receptor 2 were elevated in patients with MDD compared to HCs, whereas interferon‐gamma levels were lower in MDD (Hedge's g = −0.477, P = 0.043). Levels of IL‐1β, IL‐2, IL‐4, IL‐8, the soluble IL‐6 receptor (sIL‐6R), IL‐5, CCL‐3, IL‐17, and transforming growth factor‐beta 1 were not significantly altered in individuals with MDD compared to HCs. Heterogeneity was large ( I 2 : 51.6–97.7%), and sources of heterogeneity were explored (e.g., age, smoking status, and body mass index). Conclusion: Our results further characterize a cytokine/chemokine profile associated with MDD. Future studies are warranted to further elucidate sources of heterogeneity, as well as biosignature cytokines secreted by other immune cells.